Carbon Nanofiber Reinforced Polymer Composites - Poveda, Ronald L.; Gupta, Nikhil (SpringerBriefs in Materials,, 2016)
This book presents an extensive review of literature on the properties of carbon nanofibers (CNF) reinforced polymer composites in conjunction with advances in the production and properties of CNFs. It further provides readers a view into the development of lightweight composites whose properties are tailored and enhanced with micro- and nano-reinforcement, along with results from data comparisons from several published investigations.